Association between Body Mass Index, Waist Circumference and Gastroesophageal Reflux Disease Questionnaire Scores: A Cross-Sectional Study - Aurel Feodora Tantoro; Alwi Shahab; Ratna Maila Dewi Anggraini; Liniyanti D. Oswari; Syarif Husin (HM Publisher, 2022)
The prevalence of gastroesophageal reflux disease (GERD) has continued to increase in Asian countries in recent decades. Many studies have revealed that obesity in general or abdominal obesity causes a significant increase in the risk of GERD symptoms. This study aimed to determine the relationship between body mass index (BMI) and waist circumference with the incidence of GERD in the adult population of Palembang city. This study was observational research with a cross-sectional design. The population was all adults (≥20 years) of Palembang. The number of samples was 400 people. Data were taken from a self-completed questionnaire, distributed through social media, then analyzed using logistic regression analysis. Among 400 subjects in the study, there were 81 subjects (20.3%) diagnosed with GERD, 43 subjects (10.8%) were overweight, 79 subjects (19.8%) were obese, and 160 subjects(40%) had abdominal obesity. There was a significant relationship between obesity and diagnosis of GERD (p=0,001; OR =2,799; CI 95% = 1,545-5,069). In contrast, there was no significant relationship between being overweight and diagnosis of GERD. There was also no significant relationship between abdominal obesity and diagnosis of GERD. Obesity has a significant association with the diagnosis of GERD, but the absence of an association between overweight and diagnosis of GERD implies that increased BMI is not an independent risk factor in diagnosis of GERD.